Threat Intelligence Automation and Optimization Through SOAR Integration - Pigg, Henri (2025)
As cyber threats increase in volume and complexity, organizations must strengthen their ability to leverage threat intelligence (TI) effectively. TI aims to deliver timely, actionable information that supports the prevention and mitigation of cyberattacks. However, its real-world implementation is often limited by fragmented data, high data volume, and a lack of human resources. This study investigates how the integration of Security Orchestration, Automation and Response (SOAR) solutions into TI workflows can enhance automation, efficiency, and consistency in threat intelligence management.